Rethinking systemic change: economic evolution and institutions. Technical Paper - and Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually sound definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of the research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics, new institutional economics and complexity theory. There is a growing interest in these bodies of knowledge, combined often called New Economic Thinking, and how they affect economic development. Hence, while rethinking systemic change, this work also contributes to answering the broader question of how market systems approaches can contribute to inclusive economic development. The answer, in short, is to shift the focus away from improving transactions at the micro level towards enabling actors to continuously shape an institutional landscape that supports inclusive economic evolution. This technical paper provides an in-depth review of the fields of evolutionary economics, new institutional economics and complexity and social change. It is argued that economic development is a complex, non-linear and continuous evolutionary process. Both market and non-market institutions matter greatly in shaping economic performance. The paper then explores the consequences of this understanding for market development practice. It discusses how market development practitioners can engage in and shape an intentional change processes. To translate the theory into practice, seven principles are suggested that can be applied to market systems development practice. The paper concludes with a reframed look at systemic change in market systems development. A discussion paper presents the key messages from the literature review and seven principles drawing from this literature, and a case study offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).